The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2215/cjn.07901109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urinary Albumin-Creatinine Ratio and Albumin Excretion Rate in the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Study

Abstract: Results: Despite moderate correlation (r ‫؍‬ 0.62), ACR levels (mg/g) were lower than AER levels (mg/24 hr). This difference was greatest for men. Gender-specific estimated AER (eAER) values were empirically derived from ACR. Comparing the eAER with measured AER, agreement of prevalent microalbuminuria and macroalbuminuria classification was fair to moderate, and classification of change in albuminuria status over time was different. Intraclass correlations were 0.697 for ACR and 0.803 for AER. Effects of DCCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…Those studies that have examined the effect of gender on measured creatinine excretion or the performance of ACR have given results that are consistent and substantial (table 1) [13,16,17,18,19,20]. Warram et al [19] reported the 95th centiles of ACR in healthy men and women to be 17 and 25 µg/g, respectively, levels which also corresponded to cut points maximizing reproducibility of classification on repeat sampling.…”
Section: Adjustment For Gender Age and Racementioning
confidence: 88%
See 2 more Smart Citations
“…Those studies that have examined the effect of gender on measured creatinine excretion or the performance of ACR have given results that are consistent and substantial (table 1) [13,16,17,18,19,20]. Warram et al [19] reported the 95th centiles of ACR in healthy men and women to be 17 and 25 µg/g, respectively, levels which also corresponded to cut points maximizing reproducibility of classification on repeat sampling.…”
Section: Adjustment For Gender Age and Racementioning
confidence: 88%
“…Despite a predictive performance of PCR considered reasonable (correlation coefficient: 0.91, area under ROC curve for 1 g proteinuria prediction: 0.968), there was an almost threefold difference in the PCR threshold required to predict 1 g proteinuria with the same sensitivity in a young man or an elderly woman. Notably, not all studies have reported such strong correlations between ACR/PCR and timed urine protein excretion [13,14]. …”
Section: Correlations Of Pcr/acr With Unadjusted 24-hour Proteinuria/mentioning
confidence: 99%
See 1 more Smart Citation
“…La precisión de la relación en orina esporádica de la proteinuria/creatininuria se verá disminuida si la excreción de creatinina es sustancialmente diferente del valor esperado; esto es particularmente importante en pacientes con valores límite, por ejemplo, se subestima su valor en los hombres musculosos con una alta tasa de excreción de creatinina y se sobreestima en los pacientes caquécticos en los cuales la masa muscular y la excreción de creatinina se reducen notablemente. La proporción también varía con el género y con la raza / etnicidad en los Estados Unidos, como la excreción de creatinina es significativamente mayor entre los negros no hispanos y los estadounidenses de origen 17 mexicano que entre los blancos no hispanos .…”
Section: Evaluación De La Proteinuriaunclassified
“…ACR measurement is a precise and accurate test for kidney disease, also less likely to experience errors caused by the inaccuracy of urine collection method and variation in 24-hour urinary protein excretion. [7][8][9] Siangproh and co-worker 10 reported the determination of albumin-creatinine ratio (ACR) using spectrophotometric sequential injection analysis (SIA). Albumin was detected based on the dye-binding reaction.…”
Section: Introductionmentioning
confidence: 99%